2011
DOI: 10.4103/0976-3147.80092
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with epilepsy in India

Abstract: Background:People with epilepsy have impairment in their quality of life (QOL) due to effect of epilepsy on various aspects of their life and the medication effects. Systematic studies on QOL in epilepsy from developing countries are sparse.Objectives:To assess the QOL in people with epilepsy and to evaluate various factors affecting the QOL in them.Materials and Methods:People with generalized and partial epilepsy on medication aged more than 18 years were included in the study. The QOL was assessed with QOLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 23 publications
4
33
2
3
Order By: Relevance
“…In the present study, although lower age of onset of seizures was found to be associated with a poor QOL, a finding reported by Sinha et al [17], the seizure type did not show an association, unlike that reported in two Indian studies [4,28,29]. The clinical significance of this finding is difficult to explain.…”
Section: Qol In Pwecontrasting
confidence: 84%
“…In the present study, although lower age of onset of seizures was found to be associated with a poor QOL, a finding reported by Sinha et al [17], the seizure type did not show an association, unlike that reported in two Indian studies [4,28,29]. The clinical significance of this finding is difficult to explain.…”
Section: Qol In Pwecontrasting
confidence: 84%
“…While there is no consensus surrounding this, it is important to appreciate the chronic and serious nature of the illness and the multifaceted insecurities that notably impair QoL in these patients [26]. Around one-third of the patients in our study suffered from anxiety and 32% from depression, which may stem from obvious concerns regarding the fear of accidents, fear of losing control, and social embarrassment.…”
Section: Discussionmentioning
confidence: 98%
“…The social stigma associated with the disease can be a great social barrier for marital prospects, particularly amongst young women, in these parts of the country. Several reports have suggested lower marriage rates among people with epilepsy than in the general population and found that female gender is a major determinant of the Quality of Life (QoL) in patients with epilepsy [26-28]. The higher male ratio may also be attributed to higher incidence of head trauma and alcohol abuse in men thereby increasing the risk of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Similar to other studies, higher QOL scores in epileptic patients were associated with youth, and higher levels of education and family income. [35][36][37] It is reasonable to suggest that these factors increase the potential for social support, positive coping methods, and awareness of the disease.…”
Section: Discussionmentioning
confidence: 99%